2020
DOI: 10.1186/s12961-020-00622-9
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the paradigm: a qualitative exploration of research translation centres in the United Kingdom and Australia

Abstract: Background Over the past decade, Research Translation Centres (RTCs) have been established in many countries. These centres (sometimes referred to as Academic Health Science Centres) are designed to bring universities and healthcare providers together in order to accelerate the generation and translation of new evidence that is responsive to health service and community priorities. This has the potential to effectively ‘flip’ the traditional research and education paradigms because it requires active participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Additionally, the literature is clear that research driven by, or including, clinically active investigators results in improved translation of results and better patient outcomes [ 1 5 ], as clinicians are able to utilize their experience to shape patient- and health service-relevant research [ 4 ]. The valuable role of clinician researchers in United Kingdom and Australian research translation centres has been emphasized, as well as the need to further support and develop this workforce [ 6 ]. At a national level in Australia, “clinician researcher capability” has been identified as one of the priorities of the Medical Research Future Fund [ 7 ], and was highlighted as a key target for research capacity-building in the 2012 McKeon Review [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the literature is clear that research driven by, or including, clinically active investigators results in improved translation of results and better patient outcomes [ 1 5 ], as clinicians are able to utilize their experience to shape patient- and health service-relevant research [ 4 ]. The valuable role of clinician researchers in United Kingdom and Australian research translation centres has been emphasized, as well as the need to further support and develop this workforce [ 6 ]. At a national level in Australia, “clinician researcher capability” has been identified as one of the priorities of the Medical Research Future Fund [ 7 ], and was highlighted as a key target for research capacity-building in the 2012 McKeon Review [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 The recent UK-Australia RTC qualitative study found: "Significant challenges in integrating applied healthcare and improvement approaches with more rigorous discovery and implementation research. " 2 The authors attributed this tension to: 'Dissonant metrics between academic and healthcare sectors. ' 2 Yet awareness of the limited value to society that may be reflected in traditional academic output indicators underlies current interest in research impact assessment.…”
Section: Formative Learning and Evaluation -Where Should We Look?mentioning
confidence: 99%
“…In 2019, an AHRA steering committee proposed a National project aimed at addressing the challenges in wound care through an integrated, evidence-based approach (48). Monash Partners along with other NHMRC-accredited centres supports the integration of research, education, and clinical practise, overcoming the organisational silos and barriers to research translation (49), such as in HAPI prevention.…”
Section: Monash Partners Implementation Of the Proposed Capacity Building Frameworkmentioning
confidence: 99%